2014
DOI: 10.1186/s13054-014-0588-8
|View full text |Cite
|
Sign up to set email alerts
|

Argatroban versus Lepirudin in critically ill patients (ALicia): a randomized controlled trial

Abstract: IntroductionCritically ill patients often require renal replacement therapy accompanied by thrombocytopenia. Thrombocytopenia during heparin anticoagulation may be due to heparin-induced thrombocytopenia with need for alternative anticoagulation. Therefore, we compared argatroban and lepirudin in critically ill surgical patients.MethodsFollowing institutional review board approval and written informed consent, critically ill surgical patients more than or equal to 18 years with suspected heparin-induced thromb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 24 publications
0
20
1
Order By: Relevance
“…Regional citrate anticoagulation for CRRT was first described by Mehta et al [11] . Before, systemic UFH was the anticoagulant of choice; yet it was associated with suboptimal FLS, bleeding, and heparin-induced thrombocytopenia and thrombosis (HITT) [15,20,[22][23][24] . Premature mechanical filter failure due to clotting was also often observed and contributed to increased bedside workload and costs [2] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regional citrate anticoagulation for CRRT was first described by Mehta et al [11] . Before, systemic UFH was the anticoagulant of choice; yet it was associated with suboptimal FLS, bleeding, and heparin-induced thrombocytopenia and thrombosis (HITT) [15,20,[22][23][24] . Premature mechanical filter failure due to clotting was also often observed and contributed to increased bedside workload and costs [2] .…”
Section: Discussionmentioning
confidence: 99%
“…Premature mechanical filter failure due to clotting was also often observed and contributed to increased bedside workload and costs [2] . Recent evidence suggests that anticoagulation with citrate maintains filter patency during CRRT better than heparin with less bleeding risk and no HITT development [12,18,24] . To date, citrate anticoagulation practice relies on local protocols, customization of citrate replacement solutions, or regional pharmacy compounding.…”
Section: Discussionmentioning
confidence: 99%
“…There are no prospective studies evaluating lepirudin in children, and this drug appears to cause more bleeding than the others. 35,36 Furthermore, it is no longer marketed and thus not a therapeutic option.…”
Section: Targeted Anticoagulantsmentioning
confidence: 99%
“…Anticoagulants for hemodialysis used in China are as follows: (1) common heparin is cheap but can cause bleeding, (2) low molecular weight heparin can reduce the risk of bleeding, but still has potential risk of bleeding because of its long half-life and is difficult to be cleared through dialysis [13] , (3) regional citrate anticoagulation, although studies have shown that the proportion of bleeding complications is less than that of common heparin, as ordinary dialysate contains calcium ions, it only applies to CRRT which dialysate composition can be regulated [14] and (4) recently, some new anticoagulant drugs (such as argatroban and lepirudin) are used for hemodialysis in exceptional circumstances such as thrombocytopenia [15] . A meta-analysis showed that argatroban can significantly reduce the incidence of thrombosis and coagulation in pipeline without increasing mortality and risk of bleeding [16] .…”
Section: Preventionmentioning
confidence: 99%